Research on the Deformation Characteristics of Pressure Culvert Linings Based on Monitoring - Liang Jingwei; Wang Xiang; Cao Lei; Jiang Chu (Advances in Civil Engineering)
It is of great significance to study the deformation characteristics of the lining of a long-distance pressure culvert. The lining of a pressure culvert has the characteristics of strong concealment and remarkable influence on the whole performance. The existing research on deformation characteristics mostly adopts nondestructive detection, and the accuracy is restricted by many factors. In this paper, the lining of a pressure culvert is taken as the research object, and in situ tests of the structure are carried out and numerical simulations are conducted. Based on field monitoring data, the mechanical and deformation responses of the lining structure under external water and earth pressure are analyzed. On this basis, the finite element method is used to establish a three-dimensional finite element model, which further analyzes the deformation and mechanical characteristics of the lining structure under different conditions of internal water pressure, geological conditions, and internal water pressure alongside geological conditions. Therefore, theoretical guidance and technical support for the lining structure design of long-distance pressurized water delivery culverts are provided.